Evaluasi Sistem Distribusi Air Bersih Menggunakan Epanet 2.0 (Studi Kasus : Pdam Tirta Dharma Cabang Bengkalis) - Prayoga Wiguna; Jecky Asmura; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The Water Supply Company (PDAM) Tirta Dharma Bengkalis is a company engaged in the drinking water services, it is required to improve its service to the community in Bengkalis. The aim of this study were evaluating the existing condition of the distribution. The pressure condition of the distribution network still able to serve the needs of the service area with the residual pressure > 0.5 atm or 5 meters. From the Headloss condition, nothing criteria over the limit is above 10 m / km. Whereas for the speed condition of the distribution network, a lot of pipes do not meet the standard minimum criteria which is > 0.3 m / s, but not all the pipe need replacement especially for the main pipe with the consideration of the provision of sufficient pressure in case of the additional needs in the future. Based on the research finding, it needs preventive, so it can fulfill the future needs considering the increasing of the population that can not be avoided.Keywords: Evaluation, Water Distribution System, Modeling, EPANET 2.0